Rocky road to digital diagnostics: implementation issues and exhilarating experiences. Issue 7 (28th September 2020) - Stathonikos, Nikolaos; Nguyen, Tri Q; van Diest, Paul J
Abstract : Since 2007, we have gradually been building up infrastructure for digital pathology, starting with a whole slide scanner park to build up a digital archive to streamline doing multidisciplinary meetings, student teaching and research, culminating in a full digital diagnostic workflow where we are currently integrating artificial intelligence algorithms. In this paper, we highlight the different steps in this process towards digital diagnostics, which was at times a rocky road with definitely issues in implementation, but eventually an exciting new way to practice pathology in a more modern and efficient way where patient safety has clearly gone up.